Work-life balance in the professional sports setting: the athletic trainer`s perspective - Mazerolle, S. M.; Hunter, C. (International Journal of Athletic Therapy & Training, 2018)
The professional sport setting requires athletic trainers to work long hours, spend days on the road, and adhere to schedules made by others. These job expectations can lead to a reduction in work-life balance, and recent evidence suggests that role strain and reduced professional commitment are present. At this time, work-life balance of the professional sport athletic trainer has not been examined. Twenty-seven male athletic trainers who represented four major professional sports (NFL, NBA, MLB, NHL) participated in the study. We collected data online by asking our participants to respond to a series of demographic, Likert-scaled, and open-ended questions. Means and standard deviations were calculated for Likert scale data and scores were compiled for each question. All qualitative data from the online interviews were coded following a general inductive approach. Data source triangulation was the primary credibility strategy, followed by peer review and multiple analyst triangulation. Mean scores were 40.5 ± 6.6 for work-family/personal life conflict. Two major themes emerged from our data: barriers and facilitators. Barriers speak to those aspects of the role of the athletic trainer in the professional setting that limit work-life balance. Facilitators speak to those strategies and practices that stimulated work-life balance for our participants. The professional sports setting can be demanding and stimulate conflict, but, with support garnered from the organization and supportive spouses, balance can be gained.